Can direct gas-liquid chromatography of clinical samples detect specific organisms? - Watt, B (1982)
A total of 1929 samples was analyzed by direct gas-liquid chromatography and the volatile fatty acid (VFA) patterns of the positive samples were compared with the results of culture. There was no correlation between any bacterial genus or species and the detailed VFA patterns although the presence of butyric or valeric acids, or both, was generally associated with the presence of anaerobes and that of acetic acid was generally associated with aerobic bacteria; however, the technique could not predict the nature of the subsequent bacterial isolate. There was also poor correlation between the VFA pattern in a given sample and the VFA pattern(s) of anaerobic bacteria subsequently isolated from that sample.